P0491THE ROUTE TO INDIVIDUALIZED THERAPIES IN PRIMARY MEMBRANOUS NEPHROPATHY: BMI AND KIDNEY OUTCOMES. (6th June 2020) - Siligato, Rossella; Laudani, Alfredo; Gembillo, Guido; Calabrese, Vincenzo; Calderaro, Alessandra; Vienna, Federica giada; Laurendi, Francesco; Cernaro, Valeria; Santoro, Domenico
Abstract: Background and Aims: A real progress in treating patients more than diseases, would rest on tailored medicine and go beyond the hypothesis that "one size fits all". Glomerular diseases are not an exception to this consideration, and deserve case-by-case evaluation for choosing both the most suitable therapeutic agent and its appropriate dose, because a standardized treatment may result in worse prognosis. We analyzed the role of body mass index (BMI) in modifying renal outcomes of patients with nephrotic syndrome due to membranous nephropathy (MN) treated with immunosuppressive drugs. Method: We performed a retrospective analysis of 29 MN patients related to our center (M 19, F 10), checking their anti PLA2 R status at kidney biopsy time and any change in proteinuria, serum creatinine (SCr) and body mass index (BMI) between diagnosis and at last follow-up visit, in search of a correlation with their response to immunosuppressive treatment. Data with non normal distribution are expressed as median and interquartile range [IQR]. Results: The median follow-up of our patients lasted 49 months [IQR 14-80]. At biopsy time, almost half of them was anti-PLA2 R positive (n=14 subjects) while the other resulted to be negative and were thus screened for secondary causes of MN (n=15). Irrespective either of anti-PLA2 R status or the administration of Ponticelli regimen or Rituximab, complete remission was achieved in 31% of patients, while 34.5% experienced a partial remission and 34.5% resulted non responder to at least a therapeutic protocol. Median proteinuria reduction was of 3.732g/24h [IQR 7.636-1.77 g/24h]. Median rise in SCr was 0.140 mg/dl [IQR -0.11 – 0.4 mg/dl]. Direct association between the proteinuria/BMI ratio at diagnosis and remission of proteinuria at last follow up was statistically significant (r=-0.7506; P<0.0001) (Fig.1). Conclusion: Albeit remission is not directly correlated with basal BMI, our results appear to confirm that an appropriate drug posology, not only according to patients' renal or hepatic function but also to their body mass, may result in more effective individualized therapies in MN; nevertheless, this recorded association must be confirmed by large scale randomized clinical trials.